1996
DOI: 10.1002/(sici)1097-0142(19960101)77:1<97::aid-cncr16>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Younger women with breast carcinoma have a poorer prognosis than older women

Abstract: Our results indicate that women 40 years of age and younger have a worse 5CSS than their older counterparts. This difference in survival is not solely a reflection of more advanced disease but may reflect differences in tumor biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(89 citation statements)
references
References 18 publications
3
84
1
1
Order By: Relevance
“…These results are similar to those in previous studies in which cases were not selected to control for histologic grade or type. 3,8,12,49 Although the premenopausal women in our study presented with a higher stage of disease, overall survival in the pre-and postmenopausal women was similar. When comparing overall survival in women with high-and low-grade carcinomas, those with highgrade carcinomas had a worse prognosis, but, unexpectedly, this difference was largely a result of the particularly poor outcome of premenopausal women with high-grade carcinomas.…”
Section: Hormone Receptors and Breast Cancer Proliferationmentioning
confidence: 61%
See 2 more Smart Citations
“…These results are similar to those in previous studies in which cases were not selected to control for histologic grade or type. 3,8,12,49 Although the premenopausal women in our study presented with a higher stage of disease, overall survival in the pre-and postmenopausal women was similar. When comparing overall survival in women with high-and low-grade carcinomas, those with highgrade carcinomas had a worse prognosis, but, unexpectedly, this difference was largely a result of the particularly poor outcome of premenopausal women with high-grade carcinomas.…”
Section: Hormone Receptors and Breast Cancer Proliferationmentioning
confidence: 61%
“…Studies examining this issue have varied in design, age categorization and outcome measures. A few large population-based studies and more limited analyses [1][2][3][4][5] have indicated that women under the ages of 30 -40 years have a worse prognosis. Some retrospective studies have attempted to explain the less favorable outcome in younger women and have reported that breast cancers in younger women exhibit more adverse characteristics, including a high clinical stage at diagnosis, high histologic grade, lack of steroid hormone receptors and increased proliferation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that factors like young age and poor differentiation of triple negative cancers contribute to their aggressive nature (Mersin et al, 2008;Kwan et al, 2009;Dawood et al, 2010). These factors have been shown to be independent predictors of outcome in breast cancer patients (Adami et al, 1986;Chung et al, 1996;Sidoni et al, 2003;Sharif et al, 2010). Lack of effectiveness of hormonal therapy limits the medical options available for management of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…T h e re f o re, bre a s t cancer is mainly a post-menopausal disease, affecting around 4% of women below 35 yrs. old (Chung et al, 1996) and 7% below 40 yrs. old ( Wi n c h e s t e r, 1996).…”
Section: Introductionmentioning
confidence: 96%